2016
DOI: 10.1176/appi.ajp.2016.16010037
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Placebo-Controlled, Dose-Frequency Study of Intravenous Ketamine in Patients With Treatment-Resistant Depression

Abstract: Twice-weekly and thrice-weekly administration of ketamine at 0.5 mg/kg similarly maintained antidepressant efficacy over 15 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
283
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 422 publications
(327 citation statements)
references
References 19 publications
13
283
1
10
Order By: Relevance
“…All the patients could be discharged with no complications 30 min after the end of the infusions. Like Singh et al, 1 we also observed that the dissociative symptoms decreased with repeated doses. Two patients complained of nausea, which was successfully treated with intravenous ondansetron.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…All the patients could be discharged with no complications 30 min after the end of the infusions. Like Singh et al, 1 we also observed that the dissociative symptoms decreased with repeated doses. Two patients complained of nausea, which was successfully treated with intravenous ondansetron.…”
supporting
confidence: 85%
“…Singh et al 1 reported that two or three weekly 40 min i.v. infusions of ketamine (0.5 mg/kg) are safe and effective for maintaining an acute response to ketamine during one month of treatment for resistant depression (TRD).…”
mentioning
confidence: 99%
“…After 15 days, mean MADRS scores decreased by about 18 points in each of the 2 ketamine groups but by only 3-6 points in the 2 placebo groups. 41 An earlier, smaller, nonrandomized, open-label, naturalistic study 42 administered ketamine infusions (0.5 mg/kg) once a week (n = 15) or twice a week (n = 13) to 28 patients with unipolar or bipolar TRD. Although the authors did not formally compare the groups, from the data presented it appeared that the 2 treatment schedules yielded similar though modest antidepressant results.…”
Section: For How Long and At What Frequency?mentioning
confidence: 99%
“…A recent study showed that a twice-weekly infusion of ketamine was sufficient as an initial repeated-dose strategy [71]. Acute transient psychotomimetic and dissociative symptoms were observed, but they usually resolved within 2 h after each infusion.…”
Section: Future Directionsmentioning
confidence: 99%
“…Acute transient psychotomimetic and dissociative symptoms were observed, but they usually resolved within 2 h after each infusion. The intensity of dissociative symptoms diminished with repeated dosing [71]. Recently, Yang et al reported that repeated, intermittent administration of esketamine (10 mg/kg, once per week for 8 weeks) but not R-ketamine caused a loss of parvalbumin immunoreactivity in the prefrontal cortex of mice [72].…”
Section: Future Directionsmentioning
confidence: 99%